Conocimientos y práctica del autoexamen mamario en usuarias del Centro de Salud Rayito de Luz, cantón Machala. - Maza Vásquez, Miriam Paola (2017)
The current research is quantitative, descriptive and cross-sectional, carried out in users of 15 and 49 years of age who attend to the Health Center “Rayito de Luz”, Canton Machala, in the period September 2016-April 2017, which purpose is to determine the level of knowledge and practice of breast self-examination in this population. The universe consists of 278 patients and a sample of 107 women. The methodology was based on a survey consisting of basic questions about the knowledge and technique of breast self-examination. Within the results, it is determined that the studied population reflects the poor information they have received regarding the breast self-examination technique, so is evidenced that their knowledge is bad with a 60,7% and only the 25,2% and 14% have a good and regular knowledge respectively. The practice is inadequate in more than half of the population with 53,9% and only 46,1% perform the technique properly; However, we can highlight that the age group whose practice stands out is 36 to 49 years of age with 27,6% of women performing this procedure correctly, followed by 13,2% of women among 26 and 35 years and finally the population aged from 15 to 25 years with 5,3%. In virtue of the above it is concluded that it is of vital importance to promote the teaching of the correct breast self-examination technique, in a constant and permanent way for patients attending this health center, which will be an important prevention tool. Keywords: Knowledge and practice of breast self-examination